Small particles in Pluto's environment: Effects of the solar radiation pressure - Pires dos Santos, P. M. [UNESP]; Giuliatti Winter, S. M. [UNESP]; Sfair, R. [UNESP]; Mourão, D. C. [UNESP] (Oxford University Press (OUP), 2013)
Impacts of micrometeoroids on the surfaces of the plutonian small satellites Nix and Hydra can generate dust particles. Even in this region so far from the Sun these tiny ejected particles are under the effects of the solar radiation pressure. In this work, we investigate the orbital evolution of the escaping ejecta from both the small satellites under the effects of the radiation pressure combined with the gravitational effects of Pluto, Charon, Nix and Hydra. The mass production rate of micron-sized dust particles generated by micrometeoroids hitting the satellites is obtained, and numerical simulations are performed to derive the lifetime of the ejecta. These pieces of information allow us to estimate the optical depth of a putative ring, which extends from the orbits of Nix to Hydra. The ejected particles, between the orbits of Nix and Hydra, form a wide ring of about 16 000 km. Collisions with the massive bodies and escape from the system are mainly determined by the effects of the solar radiation pressure. This is an important loss mechanism, removing 30 per cent of the initial set of 1 μm-sized particles in 1 yr. The surviving particles form a ring too faint to be detectable with the derived maximum optical depth of 4 × 10-11. © 2013 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: Individual; Kuiper belt objects; Pluto - planets and satellites; Rings